NEW TEACHERS’ ROLES IN THE THIRD SURROUNDINGS - Romualdo Rosario, Manuel (2014)
As a consequence of the crisis of quality in the formal education, the third surroundings (virtual surroundings), open new avenues to the education, inviting teachers and students to be part of this new educational space, modifying their teaching – learning strategies or adapting the ones that they already possess. Thus, not only is it possible to share information, but also emotions and abilities could be developed in this new space. Therefore, the teacher of the third millenium must be prepared to face this challenge as an agent with greater responsibility in the prevalence to improve the educational quality because «an education that aims at quality must be as dynamic as the same society; an education of quality must be in accordance with the social necessities that are in movement».